STUDENTS’ EXPERIENCES, CHALLENGES, AND PERCEPTIONS ON U-DICTIONARY TO IMPROVE ENGLISH PRONUNCIATION - Yonri Sudirahayu,; Nia Kurniawati,; Lidwina Sri Ardiasih, (ENGLISH JOURNAL, 2024)
This study explores the experiences, challenges, and perceptions of Indonesian senior high school students, specifically those with Sundanese mother tongue backgrounds, as they utilize the "U-Dictionary" app to enhance their English pronunciation. Employing a qualitative case study approach with semi-structured interviews, the research investigates students' experiences with the app, their challenges, and their perceptions of its features and effectiveness. Additionally, it examines the influence of cultural factors, such as Sundanese phonology, on pronunciation acquisition. Grounded in Kolb's experiential learning cycle, the analysis focuses on how the app's functionalities, including pronunciation assistance, translation tools, and interactive feedback, contribute to pronunciation development. The findings indicate that students appreciated the app's interactive and user-friendly features, which facilitated their pronunciation practice and increased their confidence in speaking English. However, they faced challenges in accurately mimicking native pronunciation due to phonological differences and occasional inconsistencies in the app's feedback. Generally, students also perceived U-Dictionary as a powerful tool for pronunciation practice besides suggesting improvements in feedback accuracy and the inclusion of more tailored exercises. This study highlights the potential of mobile technology in supporting language learning for non-native speakers with specific linguistic backgrounds, providing valuable recommendations for app developers to enhance the app's functionalities and for educators to integrate such tools effectively into their teaching practices.